Characterization of heterogeneity in NBG-18 nuclear graphite microstructure by correlative analysis of optical texture and focused ion beam transmission electron microscopy observations. (15th April 2022) - Shen, Ke; Zhang, Xue; Yu, Suyuan; Kang, Feiyu
Abstract: NBG-18 is a nuclear graphite that has been considered for use in high-temperature gas-cooled reactors planned by South Africa and China. Although many characterization experiments have been performed on NBG-18 nuclear graphite, some structural features leading to microscopic heterogeneity have not yet been noticed. In this study, a detailed correlative analysis of optical texture and results from focused ion beam transmission electron microscopy (FIB-TEM), Raman mapping, and atomic force microscopy (AFM) was performed. First, various optical texture elements were identified, including aspects of the fine optical structure (granular domains and isotropic matrix) of the NBG-18 filler. A similar dual structure was also observed in the binder (anisotropic components in an isotropic matrix), and occasionally flow-type binder structures were seen. Then, guided by the large-area optical microscopy maps, various elements were explored in detail using advanced microscopy (FIB-TEM, AFM) and spectroscopy (Raman) techniques. Thus, unexpected structural properties were revealed (local isotropy and anisotropy, orientations, lattice sizes, rosettes, local atomic order and disorder), the origins (e.g., changes during carbonization process) and future evolution (e.g., changes induced by electron irradiation) of which were discussed. Thus, this study explores a new level of microstructure complexity and heterogeneity of NBG-18 nuclear graphite. Graphical abstract: Image 1